Main anesthetic blocks for eye surgery in dogs and cats (Research, Society and Development, 2021)
The aim of the article is to review the literature on the main anesthetic blocks used in eye surgery for dogs and cats, when they should be indicated, the forms of application, the main advantages and the complications that most occur in this type of anesthesia. A narrative review was carried out, using scientific articles, monographs, theses and dissertations published and available in online databases: Periodical Capes (Coordination for the Improvement of Higher Education Personnel), SciELO (Scientific Electronic Library Online) and Google Scholar, in addition to specific books on the topic. The main anesthetic blocks used for eye surgery are retrobulbar, peribulbar and eyelid blocks, in addition to anesthesia of the ocular surface. The use of ophthalmic blocks, when performed properly, represents an effective complement to general anesthesia, since they reduce the systemic effects of drugs, decrease the need for inhaled and / or intravenous anesthetics, in addition to providing postoperative analgesia. Due to the greater proximity and care of animals by their tutors, in recent years the number of ophthalmic procedures in the clinic for dogs and cats has increased. Thus, it is important that the anesthetist has knowledge about the particularities of anesthesia in these patients, as well as about the main blocks used in the cranial region and which technique and local anesthetic are most appropriate for each type of procedure.